2019
DOI: 10.1530/jme-19-0195
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic effects of RAC1 and tumor-related RAC1b on NIS expression in thyroid

Abstract: Thyroid cancer (TC) is the most common endocrine malignancy. The sodium–iodide symporter (NIS), responsible for active transport of iodide into thyroid cells, allows the use of radioactive iodine (RAI) as the systemic treatment of choice for TC metastatic disease. Still, patients with advanced forms of TC often lose the ability to respond to RAI therapy, which results in worse survival rates. We have shown that the overexpression of RAC1b, a tumor-related RAC1 splice variant, is associated with less favorable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 47 publications
3
16
0
Order By: Relevance
“…In agreement with this hypothesis, we found that in the core of this regulatory network, alongside actin, was the small GTPase RAC1. We and others have reported that RAC1 signaling potentiates the TSH-induced transcription of the NIS (SLC5A5) gene in non-transformed thyroid cells [24], and also in MCF7 breast cancer cells, in this case through the activation of p38 MAPK signaling [59]. Here, we found that RAC1 signaling also has an important role in the posttranscriptional regulation of NIS PM residency.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In agreement with this hypothesis, we found that in the core of this regulatory network, alongside actin, was the small GTPase RAC1. We and others have reported that RAC1 signaling potentiates the TSH-induced transcription of the NIS (SLC5A5) gene in non-transformed thyroid cells [24], and also in MCF7 breast cancer cells, in this case through the activation of p38 MAPK signaling [59]. Here, we found that RAC1 signaling also has an important role in the posttranscriptional regulation of NIS PM residency.…”
Section: Discussionsupporting
confidence: 66%
“…The cells expressing the HS-YFP were selected with 250 µg/mL Hygromycin B (Santa Cruz Biotechnology [SCBT], Santa Cruz, CA, USA). PCCL3 cells expressing HS-YFP were previously described [24].…”
Section: Cell Line Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported NF-kB activation as a key mechanism through which the tumor-related RAC1b exerts its oncogenic action in the context of PTC [19]. Additionally, we have also recently shown an inverse correlation between RAC1b overexpression and NIS levels in DTCs [45]. This prompted us to explore, in the present study, the impact of the NF-κB signaling on NIS expression.…”
Section: Fig 3 Effect Of Tnf-α and Pma On Tsh-induced Iodide Uptake mentioning
confidence: 84%
“…HPRT1 and TBP were used as endogenous control genes for rat and human, respectively. RT-qPCR preformed as previously described [45]. The different cell lines were subjected to a 96h starvation period followed by stimulation with TSH (1 mU/mL for 48h).…”
Section: S1 Fig Effect Of Tsh On Nis Transcriptional Expression In Tmentioning
confidence: 99%